2016
DOI: 10.1161/strokeaha.115.011392
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin and Midregional Proatrial Natriuretic Peptide as Markers of Ischemic Stroke

Abstract: Background and Purpose Chronic infections and neuroendocrine dysfunction may be risk factors for ischemic stroke. We hypothesized that selected blood biomarkers of infection (procalcitonin, or PCT), hypothalamic-pituitary-axis function (copeptin), and hemodynamic dysfunction (midregional-pro-atrial natriuretic peptide, or MRproANP) are associated with incident ischemic stroke risk in the multiethnic, urban Northern Manhattan Study (NOMAS) cohort. Methods A nested case-control study was performed among initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…This finding supported the finding from a previous study and suggested that PCT also contributes to the inflammatory process in the clinical setting of AIS [18]. Systemic markers of inflammation have been shown to be risk markers of stroke.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding supported the finding from a previous study and suggested that PCT also contributes to the inflammatory process in the clinical setting of AIS [18]. Systemic markers of inflammation have been shown to be risk markers of stroke.…”
Section: Discussionsupporting
confidence: 91%
“…Schiopu et al [17] demonstrated a positive association between plasma PCT levels and cardiovascular risk in subjects with no previous history of acute cardiovascular events, while Katan et al [18] reported that higher levels of PCT, a marker of infection, were independently associated with ischemic stroke risk in this multiethnic, urban cohort.…”
Section: Discussionmentioning
confidence: 86%
“…Serum procalcitonin (PCT) concentrations correlate with the extent and severity of microbial invasion 6 . In a recent study nested within in the Northern Manhattan Study (NOMAS), PCT concentrations were associated specifically with small vessel stroke 7 .…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence supporting the potential role of elevated natriuretic peptides as risk factors of cognitive impairment. 9 Midregional pro-atrial natriuretic peptide (MR-proANP) has been shown to be associated specifically with cardioembolic stroke etiology 7, 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation